Exploring selective neural electrical stimulation for upper limb function restoration - Wafa Tigra; David Guiraud; David Andreu; Bertrand Coulet; Anthony Gelis; Charles Fattal; Pawel Maciejasz; Chloé Picq; Olivier Rossel; Jacques Teissier; Christine Azevedo Coste (PAGEPress Publications, 2016)
This article introduces a new approach of selective neural electrical stimulation of the upper limb nerves. Median and radial nerves of individuals with tetraplegia are stimulated via a multipolar cuff electrode to elicit movements of wrist and hand in acute conditions during a surgical intervention. Various configurations corresponding to various combinations of a 12-poles cuff electrode contacts are tested. Video recording and electromyographic (EMG) signals recorded via sterile surface electrodes are used to evaluate the selectivity of each stimulation configuration in terms of activated muscles. In this abstract we introduce the protocol and preliminary results will be presented during the conference.